Предмет: Алгебра,
автор: lizabereznaya
докажите что значение выражения (p-3)(p^2+3p+9)-p^3 не зависит от значения р
Ответы
Автор ответа:
2
(p-3)(p^2+3p+9)=p^3-3^3(разность кубов)
p^3-3^3-p^3 = -3^3=-27
p^3-3^3-p^3 = -3^3=-27
Автор ответа:
1
(p-3)(p²+3p+9)-p³=p³-27-p³=-27
----------------------------------------------
----------------------------------------------
Похожие вопросы
Предмет: Алгебра,
автор: kizarufletcher
Предмет: Алгебра,
автор: kizilovnikita1
Предмет: Английский язык,
автор: fedeckooleg794
Предмет: Алгебра,
автор: dexmi1